Un modello di dipendenza tra automatismo e responsabilità - Franco Badii (Marp Edizioni, 2020)
From the clinical experience, a number of observations were launched on a addiction model based on the significance that an in individual gives to the action attendant on dependency together with the consequent person's agency related to dependency itself together with automatism events still caused by addiction. This model presents some links with Berridge and Robinson's studies, concerning the role of the stimulus' prominence as well as the wanting's circuits as part of an addiction situation.The hypothesis put forward is that the importance related to the significance attributed by the individual on a specific behavior might determine the production of dopamine, a process which is at the root of the creation of addiction. Finally, it is also outlined how (in accordance with the model) some operational guidelines can be identified regarding the intervention on addiction phenomena.